Pengaruh ekstrak daun jambu biji (psidium guajava linn.) Terhadap biofilm enterococcus faecalis - Alyssa Devina Amalia; Taufiq Ariwibowo; Meiny Faudah Amin (Jurnal Kedokteran Gigi Terpadu, 2023)
Background: Enterococcus faecalis biofilm is one of the causes of root canal treatment failure. The success of root canal treatment is achieved by mechanical and chemical functions. Irrigation is the only way to reach areas of the root canal wall that instrumentation cannot reach. Guava (Psidium guajava Linn.) leaves contain compounds such as flavonoids, saponins, tannins, triterpenoids and essential oils which have antibacterial properties. Objective: To determine the anti-biofilm effect of guava leaf extract (Psidium guajava Linn.) on Enterococcus faecalis Methods: Microdilution method laboratory experimental study using Enterococcus faecalis ATCC 29212 culture with P. guajava leaf extract assay concentrations of 100%, 80%, 60%, 40% and 20%. Results: In testing P. guajava leaf extract against E. faecalis biofilm, it was found that 60% concentration had the highest inhibition. Conclusion: Guava leaf extract (Psidium guajava Linn.) effectively inhibits Enterococcus faecalis biofilm growth.